Sistem Koordinasi Rele Jarak Untuk Pengaman Utama Dengan Rele Arus Lebih Pada Saluran Udara Tegangan Tinggi Di Wilayah Buduran - Titik Suheta; Andy Suryowinoto; Wahyu Setyo Pambudi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The transmission system plays an important role in maintaining the continuity of the distribution of electrical energy from one region to another. Disturbances in transmission lines are caused by short circuits, overloads, lightning surges, natural disturbances and others. For this reason, a protection system is needed that is reliable and can identify disturbances quickly while protecting the disturbed part of the system from other parts that can still operate normally. However, the protection system can experience operational failure due to various factors, therefore, apart from the main protection, backup protection is needed which can work when the main protection fails to work. Distance relays can be used as primary protection as well as remote backup protection on high voltage overhead lines. Meanwhile, the overcurrent relay is used as local backup protection if the distance relay fails to work. In this paper, a protection system is designed for the Buduran Main Substation channel using a combination of distance relays as main protection and overcurrent relays as backup protection using simulation method the Digsilent Power Factory. The overcurrent relay will trip at 0.5 and 0.15 seconds. From the Load Flow results, the value is obtained = 3,615 kA, = 4,67 kA and The range impedance according to the conductor cable data at the Buduran region 0,9676, Zone1 1 0,79Ω; 80%, Zone2 1,19Ω; 120% dan Zone3 as 1,48Ω is 150%. Thus the research can be declared successful in carrying out overcurrent protection